Participation in Social Funds - Schmidt, Mary; Marc, Alexandre (World Bank, Washington, DC, 2012)
The newest Bank supported social funds are designed explicitly to increase the participation of beneficiaries in identifying and managing microprojects, with the aim of making project activities more relevant and sustainable. Features which support participation are built into the design of the funds ' management structure and of the microproject cycle. Additional time, management, and training resources are needed to assess and build the necessary capacity of local organizations; and special measures may be required to enable the most marginalized groups to participate.